Pengelolaan Pengelolaan Konten Web Menggunakan Wordpress, Canva dan Photoshop untuk Guru-Guru Wilayah Jakarta - Dian Pratiwi; Gatot Budi Santoso; Is Mardianto; Agung Sediyono; Abdul Rochman (Universitas Prof. Dr. Hazairin, SH, 2020)
Web Content Management Using Wordpress, Canva and Photoshop for Teachers of the Jakarta Region The web is a tool that has been widely used to share information with the public. However, in managing the content, not a few parties who do not know how to do it well, including high school and vocational school teachers. Therefore, WordPress-based web content management training is applied to the teachers to assist them in running and managing the web. The training began with the provision of material on designing logos and banners using Photoshop and Canva, then practice how to register domains and training in making e-commerce with WordPress Content Management System. From the results of the training evaluation questionnaire, as many as 69% of participants were satisfied in delivering the material and 100% stated that web management training was needed to be learned and applied in schools.